Peningkatan Lulusan Terdata dalam Evaluasi Pendidikan di Sekolah - Imam Ahmad; Agung Tri Prastowo; Ade Dwi Putra; Yuri Rahmanto; Shiwi Angelica Cindiyasari; Almira Devita Putri (Journal of Engineering and Information Technology for Community Service, 2023)
Alumni are one part of the existence of an educational institution. The existence of alumni at this time is one part of the accreditation assessment of an educational institution. Class XII students and alumni have understood the meaning and use of tracer study. Alumni data that is not well structured causes the school to have difficulty in managing data. In addition, alumni data in the form of paper will take up a lot of space in storage and the data is prone to loss. As a result of using this application, teachers can control and evaluate tracers according to the planned target schedule as educational evaluation and accreditation needs.